Hacking, Protection and the Consequences of Hacking Hacking, Protection and the Consequences of Hacking - Zoran Cekerevac; Zdenek Dvorak; Ludmila Prigoda; Petar Cekerevac (Communications - Scientific letters of the University of Zilina, 2018)
Understanding the term hacking as any unconventional way of interacting with some system it is easy to conclude that there are enormous number of people who hacked or tried to hack someone or something. The article, as result of author research, analyses hacking from different points of view, including hacker’s point of view as well as the defender’s point of view. Here are discussed questions like: Who are the hackers? Why do people hack? Law aspects of hacking, as well as some economic issues connected with hacking. At the end, some questions about victim protection are discussed together with the weakness that hackers can use for their own protection. The aim of the article is to make readers familiar with the possible risks of hacker's attacks on the mobile phones and on possible attacks in the announced flood of the internet of things (next IoT) devices.